2019
DOI: 10.3390/nu11030617
|View full text |Cite
|
Sign up to set email alerts
|

A Scientific Perspective of Personalised Gene-Based Dietary Recommendations for Weight Management

Abstract: Various studies showed that a “one size fits all” dietary recommendation for weight management is questionable. For this reason, the focus increasingly falls on personalised nutrition. Although there is no precise and uniform definition of personalised nutrition, the inclusion of genetic variants for personalised dietary recommendations is more and more favoured, whereas scientific evidence for gene-based dietary recommendations is rather limited. The purpose of this article is to provide a science-based viewp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…Recently, GWASs have demonstrated genetic variants associated with dietary habits in several populations, and the results of these studies could be utilized for personalized nutritional recommendations [ 34 ]. In a Japanese population, a previous GWAS indicated that the 12q24 locus was associated with several dietary habits and health outcomes [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, GWASs have demonstrated genetic variants associated with dietary habits in several populations, and the results of these studies could be utilized for personalized nutritional recommendations [ 34 ]. In a Japanese population, a previous GWAS indicated that the 12q24 locus was associated with several dietary habits and health outcomes [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review reported that personalised nutrition recommendations are of great potential for optimising outcomes of weight management interventions, while also noting that research in this area is lacking and human intervention studies are needed. 6 The potential value of personalised nutrition for weight management stems from studies indicating positive consumer attitudes towards genetic-based dietary advice, 3 7 several indications that a one-size-fits all approach to weight management is not optimal, 6 and the potential for genetically guided, actionable nutrition recommendations to help motivate changes in dietary intake. 8 According to the most recent systematic review on genetic testing behaviour change research, nutrition was found to be the most promising lifestyle component that could be motivated as a result of undergoing genetic testing, especially when the genetic intervention provided actionable recommendations.…”
Section: Bmj Nutrition Prevention and Healthmentioning
confidence: 99%
“…6 Adjusted for age, sex, ethnicity, baseline body mass index. 7 Adjusted for age, sex, center, baseline weight. 8 No information about adjustment.…”
mentioning
confidence: 99%